Praktik Fraud Dalam Perspektif Novel “Negeri Para Bedebah” Karya Tere Liye. - Oktavian Yafi Subikda; Reza Shah Fahrezi; Eva Dwi Kurniawan (Pusat Riset dan Inovasi Nasional, 2024)
This research explores the representation of bribery and window dressing practices in the novel